Negative effects of agricultural open-channel irrigation system on vertebrate populations in central Mexico - Gómez-Ortiz, Yuriana; Domínguez-Vega, Hublester; Soria-Díaz, Leroy; Rubio-Blanco, Tamara; Astudillo-Sánchez, Claudia C.; Mundo, Victor; Sunny, Armando (PeerJ, 2024)
Linear infrastructures such as agricultural irrigation channels produce physical changes and negative impacts to habitats, wildlife populations, communities, and ecosystems. Open irrigation channels act as a pitfall for wildlife and can affect vertebrates of all sizes. Nonetheless, small channels have received relatively little attention by conservation biologists. The objective of this study was to analyze vertebrate species richness and mortality in relation to different sections of an irrigation channel system and the surrounding landscape characteristics. For two years, we conducted monthly surveys along an open-channel irrigation system to estimate its effect on vertebrates through records of dead and alive individuals. We examined the spatial relation of species richness and mortality with transects using a canonical correspondence analysis and chi-squared tests to determine possible variations in the different structures of the channel and seasonality. Further, a landscape diversity index was used to analyze the importance of surrounding habitat structure and composition on these parameters. Most vertebrates (61%) were found dead, small mammals and reptiles were the most affected. Our results indicate that mortality of small vertebrates varies depending on species, structures of the open-channel agricultural irrigation system (i.e., concrete channel and floodgates), seasonality (i.e., wet, and dry), and landscape heterogeneity (i.e., high, medium, and low landscape diversity). The open-channel irrigation system is a threat to populations of small vertebrates in anthropized landscapes, conservation efforts should be directed at protecting water bodies and restructuring the open-channel agricultural irrigation system to avoid mortality of species such as small rodents (M. mexicanus) and reptiles (C. triseriatus, B. imbricata, and Thamnophis spp.).
Keywords: Wildlife mortality; Linear infrastructures; Reptiles; Small mammals; Anthropization; Anthropized landscapes; Human-made infrastructures